The Prognostic Value and Function of HOXB5 in Acute Myeloid Leukemia - Chen, Miao; Qu, Yi; Yue, Pengjie; Yan, Xiaojing (Frontiers in Genetics, 2021)
Abstract Background: Currently, cytogenetic and genetic markers are the most important for risk stratification and treatment of patients with acute myeloid leukaemia (AML). Despite the identification of many prognostic factors, relatively few have made their way into clinical practice. Therefore, the identification of new AML biomarkers is useful in the prognosis and monitoring of AML and contributes to a better understanding of the molecular basis of the disease. Homeobox (HOX) genes are transcription factors that lead to cell differentiation blockade and malignant self-renewal. However, the roles of HOX genes in AML are still not fully understood and need further exploration, which may provide new strategies for the prognosis and monitoring of AML. Methods: We analysed the RNA sequencing and clinical data from the Cancer Genome Atlas (TCGA), VIZOME, GSE13159 and GSE9476 cohorts. Analyses were performed with GraphPad 7, the R language and several online databases. We applied qPCR, WB, CCK-8 cell proliferation assays and flow cytometry to verify the conclusions of the bioinformatics analysis. Results: We identified HOXB5 as the only gene among the HOX family that was not only elevated in AML but also a significant prognostic marker in AML patients. HOXB5 was highly expressed in AML patients with NPM1, FLT3 or DNMT3A mutations and was expressed at the highest level in patients with NPM1-FLT3-DNMT3A triple-mutant AML. Gene ontology (GO) analysis and gene set enrichment analysis (GSEA) revealed that HOXB5 showed a negative correlation with the myeloid cell differentiation signature and that the TNF/NF-κB signalling pathway was involved in the molecular mechanism. Moreover, we performed in silico protein-protein interaction (PPI) analysis and 450K TCGA DNA methylation data analysis and found that HOXB5 interacted with two HOX genes (HOXA7 and HOXB4) that were commonly regulated by DNA methylation levels. Conclusions: HOXB5 is associated with the malignant development of AML and may be a treatment target and biomarker for AML prognosis prediction.